Increase in Cancer Patient Load during COVID-19 Pandemic: The Faridabad Experience - Gupta, Sumant; Pandey, Anamika; Gupta, Neha; Naim, Faran; Gupta, Rakesh; Das, Bhaskar (South Asian Journal of Cancer, 2021)
Introduction Coronavirus disease 2019 (COVID-19) has affected oncology care differently across the world. We evaluated our experience of infusional chemotherapy during the active phase of ongoing pandemic.Methods Prospectively collected month wise data from January 2019 to November 2020 was compared between the 2 years.Results A total of 6,003 chemotherapy infusions were administered between January 1, 2019 and November 30, 2020 (2,548 in 11 months of 2019 and 3,455 in the same 11 months of 2020). Between May 1 and October 31, 2020, 2,337 chemotherapy infusions were administered to 570 patients all of whom were also tested for COVID-19 positivity, of which 65 (11.4%) were COVID-19 positive. The majority (63/65; 97%) could receive their chemotherapy infusions safely.Discussion Paradoxically, our hospital recorded an increase in the number of cancer patients receiving infusional chemotherapy in 2020, with a linear increase in the cancer case being treated (from 309 in June to 398 in November 2020). We believe that this was possible because cancer patients wanted treatment near their homes to avoid/minimize risk of exposure to COVID-19, cross state border travel restrictions was an additional roadblock, and our quality of service provided earned the trust of cancer patients.
Keywords: chemotherapy; treatment compliance; patient referral; logistics; India; Haryana; oncology